Transformation of Curriculum Administration in the Era of the Merdeka Curriculum: Opportunities for Flexibility and Challenges of Teachers’ Administrative Workload - Ali Maulida; Asyiroh Islami; Indri Machtifaliandri; Samsuddin (IJCRE - International Journal of Culture, Religion, and Education, 2026)
Curriculum administration is an essential element in ensuring that educational implementation runs effectively, consistently, and in accordance with students’ needs. This study emphasizes that curriculum administration is not merely an administrative activity but also plays a strategic role in linking curriculum documents with classroom learning practices. Using a literature review method, this study examines literature related to curriculum planning, implementation, supervision, and evaluation, as well as the challenges that arise in curriculum implementation. The findings indicate that learning flexibility is a key factor; however, an increase in administrative workload can reduce teaching time, cause teacher stress, and limit innovation. Therefore, the success of curriculum administration depends on balancing administrative demands with pedagogical needs, as well as the active involvement of all stakeholders, including school principals, teachers, educational staff, and the educational community. The integration of technology and professional development has also been shown to support the efficiency of curriculum management. Through adaptive, collaborative, and responsive approaches, curriculum administration is able to improve learning quality, student achievement, and schools’ capacity to respond to contemporary changes. This study affirms that curriculum administration should be viewed as a strategic instrument that supports the comprehensive and sustainable achievement of educational goals in Indonesia.